Relationship of the antibody level between male and female SARS-CoV-2 infected patients in Dhaka city - Chowdhury, Indira; Mishu, Farzana Akonjee; Tanjilul Haque, Syed Mohammad; Chanda, Papon Kumar; Mollah, Forhadul Hoque (Anwer Khan Modern Medical College Journal, 2021)
Background: The Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) created an emergency situation experienced by the world. Objective: To compare the antibody status after SARS-CoV-2 infection in male and female patients. Methods: This cross-sectional study was conducted in the Department of Biochemistry and Molecular Biology, BIRDEM General Hospital, from July, 2020 to June, 2021. A total of 154 patients (age 18 – 70 years) infected by SARS-CoV-2 were enrolled for this study. Among them, 78 were male and 76 were female. The study subjects were non-vaccinated. For this study, serum IgG level was measured by the automated analyser. For statistical analysis, the Mann Whitney U test was done. Results: the age distribution of male and female patients. The age group of 50-59 years comprised most of the male patients in comparison to the female study group. Patients with hypertension, diabetes mellitus were more prone to SARS-CoV-2 infection in both groups. Here male patients had more positive history of comorbidities than female patients. Mann-Whitney U test was done to analyze the data which revealed presence of significantly higher IgG in female patients. Here, p <0.02 which was fairly statistically significant. Conclusion: The antibody level of female patients was significantly higher than that of male patients after SARS-CoV-2 infection. AKMMC J 2022; 13(1) : 32-36